DNA Sequence Analysis of Regions Surrounding bla(CMY-2) from Multiple Salmonella Plasmid Backbones - Giles, W. P. (American Society for Microbiology, 2004)
The emergence in the United States of resistance to expanded-spectrum cephalosporin (e.g., ceftriaxone) within the salmonellae has been associated primarily with three large (>100-kb) plasmids (designated types A, B, and C) and one 10.1-kb plasmid (type D) that carry the bla(CMY-2) gene. In the present study, the distribution of these four known bla(CMY-2)-carrying plasmids among 35 ceftriaxone-resistant Salmonella isolates obtained from 1998 to 2001 was examined. Twenty-three of these isolates were Salmonella enterica serotype Newport, 10 were Salmonella enterica serotype Typhimurium, 1 was Salmonella enterica serotype Agona, and 1 was Salmonella enterica serotype Reading. All 23 serotype Newport isolates carried a type C plasmid, and 5, 4, and 1 serovar Typhimurium isolate carried type B, A, and C plasmids, respectively. Both the serotype Agona and serotype Reading isolates carried type A plasmids. None of the isolates carried a type D plasmid. Hybridization data suggested that plasmid types A and C were highly related replicons. DNA sequencing revealed that the region surrounding bla(CMY-2) was highly conserved in all three plasmid types analyzed (types B, C, and D) and was related to a region surrounding bla(CMY-5) from the Klebsiella oxytoca plasmid pTKH11. These findings are consistent with a model in which bla(CMY-2) has been disseminated primarily through plasmid transfer, and not by mobilization of the gene itself, to multiple Salmonella chromosomal backbones.